Growth of Sweet Corn (Zea mays saccharata (Sturt.) Bailey) and Weed Density With Different of Fertilizer’S Doses - Halim Halim; Tresjia Corina Rakian; Rachmawati Hasid; Resman Resman; Waode Siti Anima Hisein (UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to determine the response of the growth of sweet corn plants and weed density to the treatment of bio-fertilizer based on arbuscular mycorrhizal fungi and cow manure fertilizer. The study was conducted using a randomized complete block design (RCBD) in a factorial pattern. The first factor was arbuscular mycorrhiza fungi (AMF) consisting of four doses, namely without AMF (A0), AMF 5 g/planting hole (A1), AMF 10 g/planting hole (A2), AMF 15 g/ planting hole (A3). The second factor was cow manure fertilizer con-sisting of three doses, namely without cow manure fertilizer (B0), cow manure fertilizer 3 kg/plot (B1), cow manure fertilizer 6 kg/plot (B2). The treatment applied consisted of 12 combinations of treatments with 3 replications, so there were 36 experimental units. The observed variables were plant height, stem diameter, leaf area and weed density. The results showed that the average height of sweet corn was best at 42 DAP in the treatment of cow manure fertilizer 6 kg/plot (B2) as 111.6 cm. The average highest of stems diameter was at 14 DAP in the treatment of cow manure fertilizer 6 kg/plot (B2) as 0.40 cm. The average leaf area of sweet corn was at the age of 28 DAP was highest in the combination treatments cow manure fertilizer 6 kg/ plot (A0B2) and without AMF as 894.5. The weed species with the highest density found was I.cylindrica as 0.5-32.4%, C. kyllingia as 1.3-41.8%, C. rotundus as 1.3-30.3% and F.miliaceae as 1.2-12.7%.